Konservasi Kupu-Kupu Penting Sebagai Penyerbuk di Kampung Wisata Isyo Hills Rhepang Muaif Nimbokrang, Kabupaten Jayapura - Warikar, Evie L.; Ramandey, Euniche R.P.F.; Waisimon , Alexandra (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
Butterflies are an important example of pollinating insects of the Order Lepidoptera. The presence of butterfly pollinating insects in nature is highly dependent or influenced by the availability of flowering plants visited in the ecosystem. The purpose of this study was to determine the diversity and abundance of butterfly pollinator in flowering plants. A direct survey method (visual) with a radius of ± 100-250 m² was done with scan sampling technique. Parameters measured were the abundance and the species richness of butterflies visited flowering plants as well as the species richness of flowering plants visited by butterflies pollinator. The data obtained were analyzed using the the Shannon-Wiener diversity index (H’). The results showed that at study sites in secondary forest habitats and yards, 25 species of butterfly pollinators were found consisting of 5 families with 308 individuals. Nine species of flowering plants visited by butterfly pollinators. The Jatropha integerrima was the most visited by butterfly pollinators with 11 species, followed by Hibiscus rosa-sinensis and Ixora coccinea (9 species), Clerodendron paniculatum (6 species), Mussaenda ralateensis (4 species), Bidens pilosa and Celosia argentea (3 species), Zinnia elegans visited by 2 species and Portulaca oleracea visited by 1 species of butterfly pollinators. Based on the calculation, the value of Shannon-Wiener index (H') is 2.946, which indicates that the level of diversity of butterfly pollinators in the medium category.